Molecular Characterization and In Silico Analyses of Maurolipin Structure as a Secretory Phospholipase A2 (sPLA2) from Venom Glands of Iranian Scorpio maurus (Arachnida: Scorpionida) - Parisa Soltan-Alinejad; Hamzeh Alipour; Aboozar Soltani; Qasem Asgari; Amin Ramezani; Davood Mehrabani; Kourosh Azizi (Journal of Tropical Medicine)
The venom is a mixture of various compounds with specific biological activities, such as the phospholipase  A2 (PLA2) enzyme present in scorpion venom. PLA2 plays a key role in inhibiting ryanodine receptor channels and has neurotoxic activity. This study is the first investigation of molecular characterization, cloning, and in silico analyses of PLA2  from Iranian Scorpio maurus, named Maurolipin. After RNA extraction from S. maurus venom glands, cDNA was synthesized and amplified through RT-PCR using specific primers. Amplified Maurolipin was cloned in TA cloning vector, pTG19. For in silico analyses, the characterized gene was analyzed utilizing different software. Maurolipin coding gene with 432 base pair nucleotide length encoded a protein of 144 amino acid residues and 16.34 kilodaltons. Comparing the coding sequence of Maurolipin with other characterized PLA2  from different species of scorpions showed that this protein was a member of the PLA2  superfamily. According to SWISS-MODEL prediction, Maurolipin had 38.83% identity with bee venom PLA2  with 100% confidence and 39% identity with insect phospholipase A2 family, which Phyre2 predicted. According to the three-dimensional structure prediction, Maurolipin with five disulfide bonds has a very high similarity to the structure of PLA2 that belonged to the group III subfamily. The in silico analyses showed that phospholipase A2 coding gene and protein structure is different based on scorpion species and geographical condition in which they live.